Role of ultrasound compared to MRI in the assessment of nerve entrapment in osteofibrous tunnels in the upper extremity - Samira Elsayed Ahmed Saraya; Lamia Medhat Afifi; Mamdouh Mahfouz Ali; Manar Hussien Abdelsattar (Cairo : Samira Elsayed Ahmed Saraya, 2012)
In the third case, the patient has symptoms of nerve entrapment at one of the osteofibrous tunnels but demonstrates no discernable pathology in the oseofibrous tunnels or the nerves within. MRI examination is done for more detailed assessment of the osteofibrous tunnel. This is combined with nerve conduction studies for the evaluation of the nerves from the cervical roots to the hand to exclude intrinsic pathology of the nerve or a possible focal disease somewhere else along its course
Thesis (Ph.D.) - Cairo University - Faculty of Medicine - Department of Radio-diagnosis
Issued also as CD
Keywords: Electromyography; Proton density; Ultrasound